Encapsulation of Cardamom Essential Oil in Chitosan Nano-composites: In-vitro Efficacy on Antibiotic-Resistant Bacterial Pathogens and Cytotoxicity Studies - Jamil, Bushra; Abbasi, Rashda; Abbasi, Shahid; Imran, Muhammad; Khan, Siffat U.; Ihsan, Ayesha; Javed, Sundus; Bokhari, Habib; Imran, Muhammad (Frontiers in Microbiology, 2016)
Natural antimicrobial agents, particularly essential oils present an excellent alternative to current antibiotics due to their potent and broad-spectrum antimicrobial potential, unique mechanisms of action and low tendency to induce resistance. However their potential as a viable therapeutic alternative is greatly compromised due to their hydrophobic and volatile nature. The objective of the current research was to explore the anti-pathogenic potential of essential oils in a bio-based nano-carrier system. Six different essential oils were tested on multi-drug resistant bacterial pathogens. However, cardamom oil was selected for nano-encapsulation because of most potent anti-microbial activity. Cardamom oil loaded chitosan nano-particles were prepared by ionic gelation method with an encapsulation efficiency of more than 90% and size was estimated to be 50-100 nm. The Zeta potential was more than +50 mV that indicate a stable nano-dispersion. Cytotoxicity analysis indicated non haemolytic and non-cytotoxic behaviour on Human Corneal Epithelial Cells and HepG2 cell lines. Cardamom oil loaded chitosan nano-particles were found to exhibit excellent anti-microbial potential against extended spectrum β lactamase producing Escherichia coli and methicillin resistant Staphylococcus aureus. Our results suggested safety and efficacy of cardamom oil loaded chitosan nano-particles for treating multi drug resistant pathogens hence offer an effective alternative to current antibiotic therapy.